مستقبل الرهان على الطاقات المتجددة لعينة من الدول العربية الإمكانات والمعوقات (مجلة الواحات للبحوث والدراسات, 2015)
The arabe countries acquires at a huge and tremendous wealth of fossil energy based primarily in the oil and natural gas that enable it assumed an important place in the global power supply market, in despite of the huge potential possessed by the arabe world of the traditional sources of energy and its positive role in the economies of the arab countries, it is seeking like the rest of countries in the world for investesment in renewable energy and increase the proportion of its contribution of the total energy consumed gradually achieve the reuquirements of the continuous development, but the replacement process and the use of renewable  energy in the arab countries is not easy it is contained at a lot of obstacles and challenge.Key words : renewable energy, sustainable development, fossil energy, the arab countries.